Properties of polypropylene composite using resak saw dust as fillers (unscreened and 40 mesh size) / Mohd Fauzi Ahmad - Ahmad, Mohd Fauzi (2005)
The characteristic of polypropylene composite have been studied to knew their strength properties and the material physical properties which been mix between risk (vatica cuspidata) saw dust and polypropylene. There was mesh 40 that have higher strength value and its physical properties are good than "unscreen sample". In conclusion, "mesh 40" sample is suitable to used in industry or indoor to avoid wasting the wood. I hope the all the data can be used as a guide to see the ability of polypropylene composite from Resak species for indoor used.